Kelimpahan dan Keanekaragaman Fitoplankton Di Danau Siombak Marelan Medan - Muhammad Fariz; Puji Prastowo; Abdul Hakim Daulae (BEST Journal (Biology Education, Sains and Technology), 2026)
The organisms that are most affected when pollutants enter the water are phytoplankton, because they can respond quickly to environmental changes and float passively in the water column. Phytoplankton contain chlorophyll, which they use for photosynthesis, so they are also referred to as plant plankton. In addition, phytoplankton play an important role as primary producers and oxygen generators, serving as the main food source for aquatic organisms, particularly zooplankton. The presence of phytoplankton is an indicator of whether a body of water is fertile, and it is also used to determine phytoplankton density in a given area. The phytoplankton community is influenced by physical and chemical factors of the water. A lower level of phytoplankton diversity indicates a higher level of pollution and ecosystem degradation. One of the main causes of aquatic ecosystem damage is water pollution due to accumulated waste.This study aims to analyze species composition, diversity levels, abundance, and the relationship between environmental conditions and phytoplankton abundance in Lake Siombak, Marelan, Medan. Sampling was conducted at five stations representing different activities and water characteristics. Phytoplankton identification was carried out using a Sedgwick Rafter Cell, while the measured physical-chemical parameters included temperature, transparency, pH, DO, and BOD. Data were analyzed using the Shannon–Wiener Index and one-way ANOVA to determine differences in abundance among stations.The results showed that four phytoplankton divisions were found, consisting of a total of 21 species, dominated by Bacillariophyta and Chlorophyta. The phytoplankton diversity level was classified as very good, with an average H’ value of 2.406 and a total value of 2.623, indicating a stable community. Phytoplankton abundance reached an average of 8,608 cells/L, falling into the lightly polluted oligotrophic category. The water quality parameters indicated lightly polluted conditions, with a temperature of 22.38°C, transparency of 26 cm, pH of 6.612, DO of 5.428 mg/L, and BOD of 9.482 mg/L. The ANOVA test showed a significance value of 0.418 (p 0.05), indicating no significant difference in phytoplankton abundance among stations, which reflects relatively homogeneous environmental conditions. Overall, Lake Siombak has a stable phytoplankton community structure, but the waters are in a lightly polluted state, indicating the need for further management to maintain the lake’s ecosystem quality.